2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7590949
|View full text |Cite
|
Sign up to set email alerts
|

In vivo characterization of genetic expression of virus-transduced calcium indicators in retinal ganglion cells using a low-cost funduscope

Abstract: Virus-transduced calcium indicators are effective reporters of neural activity, offering the advantage of cell-specific labeling. To track the level of in vivo expression of genetically encoded calcium indicators (GECIs) in rodent retina, we developed a noninvasive imaging approach based on a custom-modified low-cost and simple fundus system that enabled us to monitor and characterize in vivo bright-field and fluorescence retinal image. The system clearly resolves individual retinal ganglion cells (RGCs) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The data were acquired from 3 to 4 well-expressed regions of each retina. (From[18] © 2016 IEEE. Reprinted, with permission, from Annual International Conference of the IEEE Engineering in Medicine and Biology Society IEEE Engineering in Medicine and Biology Society Annual Conference 2016.…”
mentioning
confidence: 99%
“…The data were acquired from 3 to 4 well-expressed regions of each retina. (From[18] © 2016 IEEE. Reprinted, with permission, from Annual International Conference of the IEEE Engineering in Medicine and Biology Society IEEE Engineering in Medicine and Biology Society Annual Conference 2016.…”
mentioning
confidence: 99%
“…More recently ( Borghuis et al, 2011 ), the viral transfection of the RGCs with either GCaMP3 or similar indicators has been shown to provide a stable expression of the calcium indicators as well as valuable and precise information about the spatial patterns of the retinal activation ( Borghuis et al, 2011 ; Weitz et al, 2013 ). In addition to these in-vitro investigations, the feasibility of imaging both the expression patterns and functionality of RGCs expressing GECI in vivo using adaptive ( Bar-Noam et al, 2016 ; Li et al, 2022 ) optics as well as other systems ( Schejter et al, 2012 ; Chang et al, 2016 ; Weitz et al, 2013 ; Cheong et al, 2018 ) has been demonstrated by several groups. This approach depends on the viral transfection of the GECIs, which limits the extent of the expression region and suffers from issues such as toxicity, non-uniform expression level, and decay over time ( Dana et al, 2014 ; Li et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%